Evaluation and character association study for tuber yield, biochemical and antioxidant properties of sweet potato (Ipomoea batatas) - TALANG, H D; JHA, A K; DEVI, M B; MAWLONG, G T; BIAM, KAMNI P; MAWLEIN, J; RYMBAI, H; VERMA, V K; LYNGDOH, B; HAZARIKA, S (The Indian Journal of Agricultural Sciences, 2024)
A study was carried out during 2022 and 2023 at ICAR-Research Complex for North-Eastern Hill Region, Umiam, Meghalaya to evaluate the yield, biochemical and antioxidant properties of 49 accessions of sweet potato [Ipomoea batatas (L.) Lam.] in mid hill condition of north-eastern region. The experiment was laid out in randomized block design (RBD) with 3 replications. Results indicate that Mynthlu Orange exhibited the highest tuber weight, length, diameter and yield. In terms of biochemical parameters, Meghalaya Local recorded the highest dry matter content; Col-6 recorded the highest starch content; and X-24 had the highest total sugar content. Among antioxidants, X-24 showed the highest total phenolic content, highest FRAP assay value and anthocyanin with lowest IC50 value which signified that X-24 had the highest antioxidant activity. Correlation study revealed significant positive correlation of tuber yield with tuber weight, diameter and total anthocyanin. Based on the mean performance, accessions Mynthlu Orange, X-24 and Col-6 were found promising for yield, biochemical and antioxidant parameters.